Predictors of Hospital Mortality in Patients with Atrial Fibrillation and Stroke - D.M. Akpanova; D.A. Ospanova; S.F. Berkinbayev; A.T. Mussagaliyeva; A.M. Grjibovsk (Journal of Pharmacy and Nutrition Sciences, 2019)
Atrial fibrillation is one of the most common cardiac arrhythmias; it accounts for about a third of all hospital admissions for cardiac arrhythmias. Currently, there is a tendency of aging of the population and an increase in overall life expectancy, which will further lead to an increase in the number of patients with atrial fibrillation. Usually atrial fibrillation is associated with a number of symptoms such as palpitations, interruptions, shortness of breath, pain in the heart area, fatigue, dizziness and syncopal states, but at the same time the course of both paroxysmal and permanent atrial fibrillation may not be accompanied by obvious symptoms or a noticeable decrease in quality life. Such asymptomatic atrial fibrillation is usually diagnosed by chance during an examination and can be considered a clinical finding. According to a number of studies, every third to fifth patient with atrial fibrillation was asymptomatic, and in a recently completed study in patients with paroxysmal atrial fibrillation, more than 50% of all episodes of arrhythmia were asymptomatic. When newly diagnosed atrial fibrillation, the asymptomatic form may occur in 83.2% of cases [1]. The purpose of the research is on the basis of studying the clinical features of the course of atrial fibrillation, determine the effect of asymptomatic arrhythmia on the development of fatal complications and patient survival in various forms of atrial fibrillation and develop a therapeutic strategy for managing patients with asymptomatic atrial fibrillation for the first time.